Meet and Greet Session APB with Mensa Penang Chapter - Ganasan, Marcia Jane, Dr.; Nayan, Surina (Institut Kualiti dan Pengembangan Ilmu (InQKA), 2024)
On the 2nd of April 2024, a meeting was hosted by the Academy of Language Studies (APB) UiTM Cawangan Perlis with delegates from Mensa Penang Branch. The meeting was attended by Dr. Latisha Asmak Shafie, Head of the Study Center of APB, Puan Surina Nayan, Puan Azalia and Dr. Marcia Jane. Representing Mensa Penang were Mr. Noel Yeoh, the Chairman of Mensa Penang, along with Mensans Mr. Jayaram Menon, also the founder of Roadrunner and Mr. Yeoh Ban Lye. These accomplished individuals have a penchant for designing puzzles that challenge the boundaries of logical and reasoning thinking.